The escape - Baldacci, David
It's a prison unlike any other. Military discipline rules. Its security systems are unmatched. None of its prisoners dream of escaping. They know it's impossible. Until now ... John Puller's older brother, Robert, was convicted of treason and national security crimes.
Keywords: Escaped prisoners; Brothers; Thrillers (Fiction)